Molecular Characterization of Extended-Spectrum Beta Lactamase- and Carbapenemase-Producing Pseudomonas aeruginosa Strains from a Malaysian Tertiary Hospital - Phoon, H.Y.P.; Hussin, H.; Hussain, B.M.; Thong, Kwai Lin (Mary Ann Liebert, 2018)
Pseudomonas aeruginosa infections account for high morbidity and mortality rates worldwide. Increasing resistance toward β-lactams, especially carbapenems, poses a serious therapeutic challenge. However, the multilocus sequence typing (MLST) of extended-spectrum beta lactamase (ESBL)- and carbapenemase-producing clinical P. aeruginosa has not been reported in Malaysia. This study aimed to determine the antibiotic susceptibility profiles, resistance genes, pulsotypes, and sequence types (STs) of clinical P. aeruginosa from a Malaysian tertiary hospital. These characteristics were analyzed by disk diffusion, minimum inhibitory concentration, polymerase chain reaction, pulsed-field gel electrophoresis (PFGE), and MLST for 199 nonreplicate clinical strains. The susceptibility of the strains toward the carbapenems and piperacillin–tazobactam was the lowest (≤90%), while ≥90% of the strains remained susceptible to all other classes of antimicrobial agents tested. The multidrug-resistant strains displayed high level resistance to cephalosporins (48 to ≥256 mg/L) and carbapenems (4–32 mg/L). Eleven strains harbored class 1 integrons containing blaGES-13, blaVIM-2, blaVIM-6, blaOXA-10, aacA(6′)-Ib, aacA(6′)-II, aadA6, and gcuD gene cassettes. Extra-integron genes, blaGES-20, blaIMP-4, blaVIM-2, and blaVIM-11, were also found. Overall, the maximum likelihood tree showed concordance in the clustering of strains having the same STs and PFGE clusters. ST708 was the predominant antibiotic-susceptible clone detected from the neonatal intensive care unit. The STs 235, 809, and 1076 clonal clusters consisted of multidrug resistant strains. ST235 is a recognized international high-risk clone. This is the first report of blaGES-13 and blaGES-20 ESBL-encoding gene variants and novel STs (STs 2329, 2335, 2337, 2338, 2340, and 2341) of P. aeruginosa in Malaysia.